DAMPAK PELAKSANAAN PROGRAM PENDIDIKAN GRATIS TERHADAP MINAT ORANG TUA MENYEKOLAHKAN ANAKNYA DI DESA TENGGULI - Tia Santia Sari; Amrazi Zakso; Imran Imran (Universitas Tanjungpura, 2020)
AbstractThe main problem, in this study was the impact of implementing the free education program on parents interest in sending their children to Tengguli Village. The sub problems were how the implementation of the free education program in SD and SMP in Tengguli Village, how are parents interested in sending their children to Tengguli Village, and what the impact of the implementation of the free education program on the interest of parents to send their children to school in Tengguli Village. The form of research used was qualitative research with descriptive methods. Research techniques and tools used observation guides, interview guides, and documentation tools. The results of the study stated that schools in Tengguli Village, did not have to pay for school tuition fees, the learning support facilities at the schools in Tengguli Village were quite complete and in good enough condition and can be used as learning support at schools, and the implementation of the free education program in Tengguli Village had an impact on the increasing interest of parents to send to school. Keywords: Free, Parents' Interest, School of Children